Language barrier and its relationship to diabetes and diabetic retinopathy - Zheng, Yingfeng; Lamoureux, Ecosse L.; Chiang, Pei-Chia Peggy; Anuar, Ainur Rahman; Ding, Jie; Wang, Jie Jin; Mitchell, Paul; Tai, E-Shyong; Wong, Tien Y. (BioMed Central, 2012)
Background: Language barrier is an important determinant of health care access and health. We examined the associations of English proficiency with type-2 diabetes (T2DM) and diabetic retinopathy (DR) in Asian Indians living in Singapore, an urban city where English is the predominant language of communication. Methods. This was a population-based, cross-sectional study. T2DM was defined as HbA1c 6.5%, use of diabetic medication or a physician diagnosis of diabetes. Retinal photographs were graded for the severity of DR including vision-threatening DR (VTDR). Presenting visual impairment (VI) was defined as LogMAR visual acuity>0.30 in the better-seeing eye. English proficiency at the time of interview was assessed. Results: The analyses included 2,289 (72.1%) English-speaking and 885 (27.9%) Tamil- speaking Indians. Tamil-speaking Indians had significantly higher prevalence of T2DM (46.2 vs. 34.7%, p<0.001) and, among those with diabetes, higher prevalence of DR (36.0 vs. 30.6%, p<0.001), VTDR (11.0 vs. 6.5%, p<0.001), and VI (32.4 vs. 14.6%) than English speaking Indians. Oaxaca decomposition analyses showed that the language-related discrepancies (defined as the difference in prevalence between persons speaking different languages) in T2DM, DR, and VTDR could not be fully explained by socioeconomic measures. Conclusions: In an English dominant society, Tamil-speaking Indians are more likely to have T2DM and diabetic retinopathy. Social policies and health interventions that address language-related health disparities may help reduce the public health impact of T2DM in societies with heterogeneous populations. © 2012 Zheng et al.; licensee BioMed Central Ltd.